Guidance requirements for rural women in some areas of food consumption rationalization in Kafr El Sheikh governorate - Egypt - El Deeb, Badria; Shalaby, Raja; Ibrahim, Adel; Al Shafei, Abdul Aleem (Arab Journal for Sciences and Research Publishing, 2016)
The objective of this research were to determine the Knowledge Extension Requirements of Rural Women’s in the food rationalization consumption at Saidi Salem District, Kafrelsheikh Governorate. The research population consisted of all wife’s to the farmers in Manshiat Abaas at Saidi salem district that’s is 2345 wife. A random sample of 234 respondents representing was selected. The data were collected by personal questionnaire through measuring tool consisted of five axes, this axes had 6, 24, 16, 7, and 7 items. Data were analyzed by using: Ratio, Mean, stander division, and borich function. The results showed that 80.8% of the respondents were medium and high level of knowledge extension requirements in the food rationalization consumption fields. Also, the results showed that foods arrangement was firstly, then the treatment with residual foods, then food buy, then food presenting, and determine of food needs to the family. also, the results showed that important communication channels to the respondents in the food rationalization consumption field were the mother, then husband mother, then personal experience. Finally, the agricultural extensions women were in the final arranging as communication channel to them.